Pengembangan Media Puzzle Untuk Menulis Karangan Narasi Pada Siswa Sekolah Dasar - Sobirin, Ali; Utomo, Slamet; Setiadi, Gunawan (Universitas Muria Kudus, 2022)
Problems in writing narrative essays include the use of inappropriate learning media so that students' understanding is low, it is necessary to develop learning media to write essays in the form of puzzles. The purpose of this study was to develop puzzle media in Indonesian language learning materials for writing narrative essays in Grade III elementary school. This type of research is Research and Development (RD) with the research subjects being teachers and third grade students of elementary schools in the Hasanudin Group, Kebonagung District.. The results of the research are 1) the development of puzzle media is needed based on a needs analysis of learning media in Indonesian language lessons for writing narrative essays. The development of puzzle media was chosen because it is easy to make and practical in its use. By using picture puzzle series students are challenged to compose pictures and to think creatively in completing essays 2) The quality of puzzle media development is very valid, feasible and effective to use to improve narrative essay writing skills. in the third grade of elementary school